A methane sink in the Central American high elevation páramo: Topographic, soil moisture and vegetation effects - Chai, Leanne L. (2020)
Methane (CH4) is a strong greenhouse gas with a global warming potential 23 times larger than that of carbon dioxide. Characterizing ecosystems as either sources or sinks for methane and their magnitudes informs on biosphere contributions to the global CH4 budget and to warming of the atmosphere. We quantified methane fluxes for the first time in a neotropical alpine páramo (Valle de Los Conejos, Chirripó Massif, Costa Rica) and examined the relationships of these fluxes with topography, soil moisture and vegetation, during the transition from dry to rainy season. Using closed chambers and laser spectroscopy, we measured soil CH4 and CO2 fluxes across a field site encompassing: a grassy plain as well as a plain, a gentle slope and a plateau dominated by a dwarf bamboo (Chusquea subtessellata Hitchcock). We found that the páramo landscape acts as a sink for CH4 [−53.1 ± 29.6 (mean ± SE) µg C m−2 hr−1]. Of the four field areas, the grassy plain was on average the strongest CH4 sink, likely because this soil profile had no drainage restrictions and was well aerated. By contrast, in the slope and plateau, a heavily-consolidated subsurface layer was shown to perch water, increasing surface soil moisture and limiting CH4 uptake. Conversely, in certain parts of the plain, where Chusquea grew vigorously in discrete, tall patches, we found intense CH4 uptake beneath these patches. Within the Chusquea plain, these hot spots of CH4 uptake localized under the tall Chusquea had double the uptake rates than outside these patches, with even greater uptake than the average in the grassy plain. Our results show that CH4 uptake in the páramo is driven by moisture interacting with impeding soil layers, vegetation and topography.